2020
DOI: 10.1038/s41598-020-63284-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of autotaxin in the pathophysiology of elevated intraocular pressure in Posner-Schlossman syndrome

Abstract: to examine whether autotaxin (AtX) in the aqueous humor causes elevated intraocular pressure (iop) in patients with posner-Schlossman syndrome (pSS). AtX and transforming growth factor beta (tGf-β) in the aqueous humor were quantified in PSS patients. The expression of ATX and TGF-β in cytomegalovirus (cMV)-infected-human trabecular meshwork (htM) cells was examined. Biological changes in htM cells and monkey Schlemm's canal endothelial (Sce) cells cultured in the conditioned medium of cMV-infected htM cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…Higher levels of TGF-β1 and -β3 isoforms are most commonly observed in XFG 28,31 , and it has been speculated that high IOP itself may induce the expression of activated TGF-β1 35 . Taken together with the results of our previous study on PSS 10 , TGF-β1 upregulation may reflect IOP elevation, not as the cause but the result of IOP elevation. As for TGF-β3, Vijay et al 36 reported that TGF-β3 is involved in ECM deposition by applying 1 ng/mL TGF-β3 to hTM cells for 4 weeks.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Higher levels of TGF-β1 and -β3 isoforms are most commonly observed in XFG 28,31 , and it has been speculated that high IOP itself may induce the expression of activated TGF-β1 35 . Taken together with the results of our previous study on PSS 10 , TGF-β1 upregulation may reflect IOP elevation, not as the cause but the result of IOP elevation. As for TGF-β3, Vijay et al 36 reported that TGF-β3 is involved in ECM deposition by applying 1 ng/mL TGF-β3 to hTM cells for 4 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…In that study, we also found that ATX and TGF-β1 in the AH of PSS patients are significantly correlated. Additionally, our results showed that ATX is significantly related to IOP; however, TGF-β1 is not 10 . In an in vitro study using hTM cells, both ATX and TGF-β1 were significantly upregulated during CMV infection, which mimics SOAG in vitro, whereas TGF-β1 was upregulated following ATX upregulation.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…17,[22][23][24][25][26][27][28][29][30][31][32][33][34] For instance, the bioactive lipid, lysophosphatidic acid (LPA), is elevated in the aqueous humor of patients with POAG and other forms of glaucoma. 30,31,35,36 Apart from glaucoma, LPA has been implicated in cancer, fibrosis, and chronic inflammation [37][38][39] ; and typically evokes its biological functions by binding to its G-protein-coupled receptors (i.e., LPAR1 to LPAR6). 33,38 LPA is a catalytic product of autotaxin (ATX), whose enzymatic activity and/or expression levels are also increased in POAG and mechanically stretched human TM (hTM) cells.…”
mentioning
confidence: 99%